2013
DOI: 10.1080/00958972.2013.794383
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic efficacy of an oxido-peroxido tungsten(VI) complex: synthesis, X-ray structure and oxidation of sulfides and olefins

Abstract: An oxido-peroxido tungsten(VI) complex [WO(O 2 )L(CH 3 OH)] using salicylidene benzoyl hydrazine as a tridentate ONO donor Schiff base (H 2 L) has been synthesized and characterized by elemental analysis, IR, 1 H NMR, molar conductance data, and single-crystal X-ray analysis. The complex was used as a catalyst for epoxidation of olefins and oxidation of sulfides. The results show that epoxides and sulfoxides were produced in high yield, turnover number, and selectivity. IntroductionOxido and peroxido transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Comparison of the catalytic performances presented in this work with those of other similar studies [61][62][63][64][65][66][67] reveals that our catalytic system is superior to some of the previously reported catalysts in terms of catalytic activity (TON) and reaction conditions. The high turnover number of our catalyst compared to recently reported protocols 61,62 makes the Fe 3 O 4 @SiO 2 -NH 2 @[MnTPFPP] more attractive for oxidation of hydrocarbons.…”
Section: Catalytic Experimentssupporting
confidence: 57%
See 2 more Smart Citations
“…Comparison of the catalytic performances presented in this work with those of other similar studies [61][62][63][64][65][66][67] reveals that our catalytic system is superior to some of the previously reported catalysts in terms of catalytic activity (TON) and reaction conditions. The high turnover number of our catalyst compared to recently reported protocols 61,62 makes the Fe 3 O 4 @SiO 2 -NH 2 @[MnTPFPP] more attractive for oxidation of hydrocarbons.…”
Section: Catalytic Experimentssupporting
confidence: 57%
“…According to the molar ratio of 1/250/500 for catalyst/substrate/oxidant which is carried out in this work, the amount of catalyst which is used in each run (0.01 g, containing 8 Â 10 À4 mmol of MnPor) is lower than that of previous works. [61][62][63][64][65][66] It is observed that in several articles, 62,65 performance of the catalyst in oxidation of various substrates was inspected under reux, while the oxidation reactions were carried out at room temperature in this work. It should be mentioned that the insertion of an oxygen atom within the C-H of a saturated carbon atom is one of the most difficult reactions to achieve with a catalyst at room temperature.…”
Section: Catalytic Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…All chemicals and solvents were obtained from Merck and Fluka Inc. and were used without further purification. Layered double hydroxide (LDH) with Mg 1‐ x Al x (OH) 2 (Cl) x .zH 2 O composition and WO 3 were synthesized described in previous reported procedures …”
Section: Methodsmentioning
confidence: 99%